The Cape Town affair - Webb, Robert, 1903-1990; Medford, Harold, 1911-1977; Fuller, Samuel, 1912-1997; Trevor, Claire, 1909-2000; Brolin, James, 1940-; Bisset, Jacqueline, 1944-; Twentieth Century-Fox Film Corporation; Cinetel Films ([Culver City, CA]: Twentieth Century-Fox Film Corporation, 1967)
Skip McCoy, a pickpocket in South Africa, steals a purse belonging to a shady woman named Candy. Unbeknownst to either party, the bag holds a strip of microfilm that contains secrets vital to the Cold War. Candy has been under surveillance by government agents, and McCoy soon finds himself caught between a Communist spy ring and the protectors of the free world, both of whom will stop at nothing to recover the film.
Claire Trevor, James Brolin, Jacqueline Bisset, Bob Courtney, John Whiteley, Gordon Mulholland.
Director of photography, Davide Millin; editor, Peter Grossett; music, Bob Adams, Joe Kentridge.
Dubbed into Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed November 25, 2015)
Keywords: Cape Town (South Africa) -- Drama; Spy films; Action and adventure films; Feature films; Internet videos; Streaming video